The good representative - Dovi, Suzanne Lynn, 1966-; Wiley InterScience (Online service) (Malden, MA : Blackwell Pub., 2007)
Is President George W. Bush, by democratic standards, a good or a bad representative? Who is a better representative according to democratic standards: former Rep. Tom Delay or Senator Hilary Clinton? Political theorists typically remain silent about the proper standards that democratic citizens should use for selecting their representatives. In'The Good Representative,' Suzanne Dovi argues that democratic citizens should evaluate their representatives using democratic criteria. In doing so, she provides an account of what it means to represent in a democratic fashion as well as a framework within which citizens can assess the democratic credentials of their representatives. For Dovi, good democratic representatives manifest three virtues: they must be fair-minded, build critical trust, and be good gatekeepers. Arguing that democratic representation, even good democratic representation, is not always desirable, this provocative book also prompts us to think about how democratic representation can be a tool of liberation or a tool of domination.; This timely book articulates, for the first time, a normative framework within which democratic citizens can fruitfully proceed in assessing their representatives as democratic representatives.
Cover -- Contents -- Preface -- Acknowledgments -- 1 Who is a Good Representative63; -- An Ethics of Democratic Representation -- The Proper Scope of an Ethics of Democratic Representation -- Three Assumptions -- The Theoretical Contribution of The Good Representative -- Deliberative democracy -- Descriptive representation for historically disadvantaged groups -- The Structure of The Good Representative -- 2 Moving beyond Descriptive Representation -- Democratic Representation and Descriptive Representation -- Two Problems with Descriptive Representation -- Justifying the Silence about Criteria -- The Need for Criteria -- The Need for Democratic Standards -- 3 Democratic Advocacy and Good Democratic Representation -- The Scope of Democratic Representation -- Sources of Authority for Democratic Representatives -- Holding Democratic Representatives Accountable -- Existing Standards for Identifying Bad Representatives -- The interests of the constituents -- Autonomy -- Professional norms -- Why Democratic Standards63; -- The importance of standards -- The Importance of Function -- Identifying the function of democratic representatives -- Political advocacy -- Democratic advocacy -- The Three Virtues -- Democracy and Democratic Citizens8217; Preferences -- 4 The Virtue of Fair45;Mindedness -- Political Efficacy -- Democratic Efficacy -- Why Civic Equality63; -- The Meaning of Civic Equality -- Using the First Virtue to Evaluate Representatives -- Two Problems with the First Virtue -- 5 The Virtue of Critical Trust Building -- Democratic Representation and Participation -- Problems with Evaluating Representatives by Citizen Participation -- The Virtue of Critical Trust Building -- Promoting Critical Trust -- Problems with the Second Virtue -- 6 The Virtue of Good Gatekeeping -- Developing the Right Relationships -- The Scope of Mutual Relations -- The Virtue of Good Gatekeeping -- Political opponents -- The dispossessed -- The marginalized -- A Perspective of Exclusion -- Problems with the Third Virtue -- Conclusion -- 7 Preferable Democratic Representatives58; Real45;World Political Virtues -- Preferability and the Virtues -- Preferability and System45;Dependency -- Are Good Descriptive Representatives Good Democratic Representatives63; -- Choosing among the Virtues -- Bad Democratic Representatives -- Notes -- References -- Index -- Last Page.
Includes bibliographical references (pages 228-240) and index.
Print version record.
Keywords: Representative government and representation; POLITICAL SCIENCE -- Political Ideologies -- Democracy; Representative government and representation; Electronic books